Peran Kelompok Perawatan Diri (KPD) dalam Upaya Mencegah Peningkatan Kecacatan pada Penderita Kusta - Noratikasari, Puji Dwi; Ariyanto, Yunus; Ririanty, Mury (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2020)
Background: Leprosy sufferers who were not treated immediately deteriorate their disease and increase the risk of complications such as permanent defects in skin, hands, feet and eyes. Disability in leprosy patients can be prevented by early diagnosis and routine treatment of multi drug therapy (MDT). Regular MDT only kill leprosy germs but not permanent defects that should need more optimal efforts. The role of KPD was to help lepers in facing disabilities and also to empower them in improving socio-economic status. This study aims to describe the roles of KPD in leprosy patients in Jember District. Method: This is a descriptive study which conducted in two health centers in Jenggawah and Anggrek Sumberbaru. This study involved 27 leprosy patients which selected purposively (patient with permanent defects). Data was collected using partially structured questionnaire includes open ended question and observations. Data analysed using univariate, bivariate and categorizing open ended questionnaire.Results: The role of KPD in two health centers has been conducted mostly in helping leprosy patient to do defects’ self care. The KPDs also provided counseling and training to patient and family to take routine medication. The results also showed that the limited facilities including budget for doing self care by leprosy patients was the barriers to comply take complete medication. In terms of empowering the lepers, KPDs have done minimally because of limited resources. This study recommended that to improve the socio-economic patient needs to cooperate with other sectors including private parties in order to obtain more funding.